What are The Clinical Outcomes of Arthroscopic versus Open Surgical Reconstruction for Anterior Cruciate Ligament (ACL) Injuries : A Systematic Review - Shina Niko Apredo; Jatniko Fadhilah (The International Journal of Medical Science and Health Research, 2025)
Introduction Anterior Cruciate Ligament (ACL) rupture is a common knee injury that often requires surgical intervention to restore stability and function. The primary surgical options are traditional open reconstruction and modern minimally invasive arthroscopic techniques. Despite extensive research, there is no definitive consensus on the superiority of one method over the other, prompting this systematic review to synthesize current evidence on their comparative clinical outcomes. Methods This systematic review was conducted following the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines. A comprehensive search of databases including PubMed, Google Scholar, Springer, Semantic Scholar, and Wiley Online Library was performed using PICO-based keywords to identify relevant studies. The review included randomized controlled trials and comparative observational studies that compared clinical outcomes of primary open versus arthroscopic ACL reconstruction in adult patients. Data on knee stability, functional scores, and complication rates were extracted and synthesized. Results Twenty studies were included in the final analysis. The synthesis of evidence revealed no consistent, statistically significant long-term differences between open and arthroscopic ACL reconstruction in primary outcomes, including knee stability (Lachman test, pivot-shift test, KT-1000) and patient-reported functional scores (Lysholm, IKDC). However, high rates of radiographic osteoarthritis were observed at long-term follow-up regardless of the surgical technique. Furthermore, factors such as the management of associated meniscal injuries and specific variations within arthroscopic techniques (e.g., all-inside vs. transtibial) appeared to be more influential on specific outcomes than the open versus arthroscopic approach itself. Discussion The findings indicate that both surgical methods are effective in restoring knee stability and function. The clinical debate is shifting from a simple open versus arthroscopic comparison to a more nuanced evaluation of procedural variables within arthroscopy, such as graft choice and the use of adjunctive procedures. The high incidence of long-term osteoarthritis suggests that the initial trauma may be a more critical determinant of joint health than the reconstruction method. Conclusion Arthroscopic and open ACL reconstruction techniques yield broadly comparable long-term clinical and functional outcomes. The choice of procedure does not appear to be the most critical factor for long-term success. Future research should focus on refining specific surgical techniques, developing strategies to mitigate post-traumatic osteoarthritis, and personalizing treatment based on patient-specific factors like associated injuries.